Designing Educational Motion Graphics on Brain Rot for Generation Z - Setyawan, Engeline (Titik Imaji, 2025)
The rapid development of digital technology hassignificantly influenced the lifestyle of Generation Z, particularly in their excessive consumption of short-form digital content. This phenomenon has led to a condition known as brain rot—a cognitive decline caused by continuous exposure to shallow and instant content. This study aims to design an educational medium in the form of motion graphic animation to raise awareness among Generation Z about the dangers of brain rot. Using a descriptive qualitative method, data were collected through literature studies, questionnaires, and interviews with psychologists, design practitioners, and Generation Z respondents. The analysis results show that motion graphic is an effective medium for delivering educational messages in a visually engaging way. The main output is a 3-minute animated video designed with a flat visual style, light toned narration, and supported by digital promotional media. Evaluation results indicate that most respondents understood the conveyed message and were interested in the format used. In conclusion, motion graphics can serve as a relevant educational tool to promote digital literacy and mitigate the effects of brain rot among Generation Z.